Effects of ambient air pollution on respiratory health of adults: findings from a cross-sectional study in Chandrapur, Maharashtra, India - Gawande, Uddhao; Khanvilkar, Abhijit; Kadam, Suhas; Potdar, Gurudatt; Salvitthal, Hrushikesh (International Journal of Research in Medical Sciences, 2016)
Background: Outdoor air pollution and continuous exposure to ambient air pollutants like particulate matter are among the leading contributors to adverse respiratory health outcomes all over the world. This association between air pollution and the impairment of respiratory functions is evident from number of epidemiological studies specific study has been conducted with an objective to evaluate the effects of ambient air pollution on respiratory symptoms and diseases of adults, in Chandrapur district of Maharashtra state in India. Methods: Comparative cross-sectional quantitative study was undertaken in the Chandrapur district with two geographical locations – study and control between August-November 2013. The data included primary data collection from adults to assess the lung function among adults, spirometry test was used to assess lung function. 2400 adults were selected in this study. Epidemiological information was collected from them by administering structured tool (2400) and Lung function test through spirometry (1200). Data was analysed using frequency tables, crosstab analysis and chi-square test to show significance. Results: Higher % of adults in study area (84.1%) had illness episodes (2-4 times or more than 4 times) compared to control area (78.3%). Statistically significant difference is observed in prevalence symptoms such as Dry Cough, Sneezing, Sore throat, Breathlessness and Asthma by Chi Square test between study and control groups. Statistically significant difference is observed in prevalence symptoms in Sore Throat, Sneezing, Wheeze and Breathlessness by Chi Square test between ≤ 5 km and >5km distance from the industry. Conclusion: There is a significant effect of ambient air pollution on respiratory symptoms of adults with high prevalence of the symptoms in the study area which is the industrial area than the control area. Presence of multiple industries in or near the village is more harmful than the single industry. Additionally, it also shows that the presence of steel, cement and paper industry in or near a village has caused more ill-effects as compared to coal and thermal industry.